Effect of Fumonisin-Contaminated Corn on Growth Performance of 20- to 60-lb Nursery Pigs - Z. X. Rao; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; H. Calderon Cartagena (Kansas Agricultural Experiment Station Research Reports, 2019)
This experiment was conducted to determine the effect of feeding fumonisin (FUM) contaminated corn on growth performance of 20- to 60-lb nursery pigs. A total of 350 pigs (241 × 600; DNA, Columbus, NE; initially 19.6 lb) were used. Dietary treatments consisted of FUM-contaminated corn blended with relatively FUM-free corn to provide toxin (FB1 + FB2) of 7.2, 14.7, 21.9, 32.7, and 35.1 ppm. Experimental diets were fed in mash form for 28 d. There were 5 pigs per pen and 14 replicates per treatment. After weaning, pigs were fed common diets for 21 days before the experiment started. Then, pens were assigned to treatments in a randomized complete block design with initial weight as the blocking factor. From d 0 to 28, increasing FUM decreased (linear,P<0.001) average daily gain (ADG) and final body weight (BW) and average daily feed intake (ADFI; linear,P= 0.05). Feed efficiency (F/G) became poorer as FUM increased (linear,P= 0.01). Although tested linear, the greatest reduction in ADG was observed in pigs fed greater than 21.9 ppm of FUM. Increasing FUM increased serum sphinganine (Sa) and sphingosine (So) ratios (linear,P<0.001) on day 14 and 28, which corresponded with the decreased growth performance. Data indicated that the serum Sa:So ratio is a reliable biomarker indicating FUM intoxication. These results suggest that for 20- to 60-lb nursery pigs, diets containing more than 30 ppm of FUM should not be fed, as increasing FUM concentration worsens growth performance and increases serum Sa:So ratio. Furthermore, diets containing greater than 21.9 ppm should be evaluated with caution as further research is warranted to deter- mine the fumonisin concentration between 21.9 and 30 ppm where the negative effects on pig performance are observed.
Keywords: corn; fumonisin (FUM); nursery; pigs